Effects of three intravitreal injections of aflibercept on the ocular circulation in eyes with age-related maculopathy. Issue 1 (12th April 2019) - Mursch-Edlmayr, Anna Sophie; Luft, Nikolaus; Podkowinski, Dominika; Ring, Michael; Schmetterer, Leopold; Bolz, Matthias
Abstract : Aims: To investigate changes in ocular perfusion following three consecutive intravitreal injections with aflibercept for treatment of neovascular age-related macular degeneration (nAMD). Methods: The study included 20 eyes from 20 Caucasian patients with unilateral nAMD and 20 fellow eyes. All nAMD eyes were treated with standard intravitreal injection of aflibercept (IVA; 2 mg). Measurements of ocular perfusion at the optic nerve head (ONH) and the choroid were performed with laser speckle flowgraphy (LSFG). Measurements were conducted at baseline, 1 week after the first injection, at the time point of the second and third injection as well as 1 month after the third injection. Results: In treated eyes, mean blur rate (the main output parameter of LSFG) in the ONH microvasculature and in the choroid was significantly reduced 1 week after the first IVA treatment. The effect persisted throughout the entire follow-up period (p<0.001). No change in ocular perfusion was observed in fellow eyes. Conclusions: IVA for treatment of nAMD leads to a reduction in perfusion of the ONH and the choroid in the treated eye with no apparent effect on the fellow eye.